Madagascar Economic Update : A Closer Look at Three Strategic Areas - World Bank (Washington, DC, 2017)
On the economic front, Madagascar's quest for stability has continued with persistent trends in major indicators over the last few months. Yet, the authorities have been managing strategic prices, intervening on the exchange rate market, and adopting the revised budget law. Those new actions, partly the Government's response to exogenous factors, have and influence significantly but unevenly a large variety of stakeholders. The magnitude of these impacts might in turn shape not only future policy but also political decisions.